Estereótipos e a construção identitária da população goianiense: os sentidos produzidos por interagentes do Instagram a partir do humor do Goiânia Mil Grau - Teles, Diogo Carvalho Gondim (2020)
This dissertation starts from the observation of the communicational system instituted between the comedic constructions of an Instagram profile and the identities of its followers. Thus, we seek to investigate the stereotypes of the goianiense population explored by Goiânia Mil Grau, a comedy group located in the city of Goiânia/GO, and the meanings produced by interagentes of the profile who also reside in this territory. Therefore, the representations of an imagined collectivity between different social types, cultural heritage, humor strategies and online interactions that relate to the sociocultural daily life of the city are analyzed. The dissertation’s goal is to understand how the stereotypes represented in the profile publications are appropriated by their interagentes, as a possible mediation in the construction process of this population’s identity. The methodological approach started from a perspective that brings together the dimensions of this communicational system, production/product/reception, in data collection in the online and offline fields. The results show the existence of a universe of common references between producers and interagentes from Goiânia Mil Grau, which feed feelings of belonging to the local/regional culture, marks similarities and differentiations among the inhabitants of Goiânia and promotes experiences of “laugh at yourself”.